Reconsidering the cost of job loss: Evidence from redundancies and mass layoffs - Jonas Cederlöf (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
This paper studies the consequences of job loss. While previous literature has relied on mass layof fs and plant closures for identification, I exploit discontinuities in the likelihood of displacement generated by a last-in-first-out rule used at layof fs in Sweden. Matching data on individual layof f notifications to administrative records, I find that permanent earnings losses are only found among workers losing their job in mass layof fs, whereas workers displaced in smaller layof fs fully recover. Auxiliary analysis suggests that large layof fs increase exposure to non-employment, prolong unemployment and cause workers to leave the labor force, conceivably by affecting the local labor market.
Keywords: J63; J64; J65; 330; last-in-first-out; job loss; displaced worker; mass layof f; earnings loss